Initialization protocols for TDMA in single-hop wireless network - Micic, Aleksandar (University of Ottawa (Canada), 2003)
Although collision free TDMA schemes have been proposed and used for more than two decades, an important ingredient of these schemes, the initialization of stations (that is, assigning ID numbers 1,2,...,N) was not investigated until recently. In this thesis, we propose several new randomized and deterministic initialization methods, and measure the performance of these new and some known methods. The main contributions of this thesis are new randomized hybrid algorithms for the cases of known and unknown number of users. Performance of these algorithms was evaluated by comparing it with improved versions of existing algorithms, and an improvement from e·N to approximately 2.2·N was obtained. We also proposed the first deterministic initialization algorithms, and showed that they have comparable performance to the corresponding randomized algorithms. The initialization algorithms are then incorporated into collision free TDMA schemes, which take into account the dynamic nature of network and dynamic bandwidth requirements.
Keywords: Computer Science.